Persiapan Menghadapi Dunia Kerja bagi Lulusan Mahasiswa melalui Pelatihan Kesiapan Kerja dan Penguatan Soft Skills - Mahendra Galih Prasaja; Vivid Dekanawati; Yudhanita Pertiwi; Himawan Aditya Prata (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2026)
The readiness of graduates to face the world of work is a crucial challenge amidst the increasingly competitive job market. This community service activity aims to improve student job readiness through job readiness training and strengthening soft skills. The methods used include needs analysis, CV preparation training, job interview simulations, strengthening soft skills, and pre- and post-training evaluations. The results of the activity show a significant increase in students' understanding of the world of work, self-confidence, and readiness to face the recruitment process. This activity is expected to become a model of sustainable service in increasing the competitiveness of graduates, by providing relevant and applicable provisions to face the challenges of the ever-evolving world of work. Strengthening soft skills is also expected to be a determining factor in students' success when entering the world of work. The sustainability of this program is expected to have a long-term positive impact on the development of graduates' competencies in various fields of work. In the future, the sustainability of this program is expected to have a long-term positive impact on graduates' competencies, strengthen their position in the job market, and support the development of skills needed in various fields of work that continue to evolve.